(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Lichen planus (LP), the most typical and best characterized lichenoid dematosis, is an idiopathic inflammatory skin disease affecting the skin and mucosal membranes. Classic LP typically presents as pruritic, polygonal, violaceous flat-topped papules and plaques; many variants in morphology and location also exist, including oral, nail, linear, annular, atrophic, hypertrophic, inverse, eruptive, bullous, ulcerative, lichen planus pigmentosus, lichen planopilaris, vulvovaginal, actinic, lichen planus-lupus erythematosus overlap syndrome, and lichen planus pemphigoides. Clinical presentation of the rarer variant lesions may be largely dissimilar to classic LP and therefore difficult to diagnose based solely on clinical examination. This article contains an array of reports on the forms in presentation and successful management of LP and its variants. A familiarity with LP and its variants is important in achieving timely recognition and management of the dermatoses.